Penghapusan Pidana Terhadap Pelaku Pembelaan Diri Yang Mengakibatkan Hilangnya Nyawa Oranglain Ditinjau Menurut Kuhp (Analisis Putusan Nomor 61/Pid.B/2019/PN. Cbd) - Mahdiyan Tri Wahyudi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
A person who is forced to do an act to defend himself or another person because of an attack on himself or another person, against his own or others' moral honor or against his own property or another person, cannot be punished. Therefore, many times people use the excuse of a forced defense (noodweer) with the hope that what they have done has fulfilled the elements or conditions of a forced defense as referred to in Article 49 paragraph (1) of the Criminal Code.The formulation of the problem in this thesis is how to regulate the legal abolition of criminal acts of self-defense that result in the loss of other people's lives, how is the criminal liability of perpetrators of self-defense resulting in the loss of other people's lives, what are the legal considerations of judges for abolition of crimes in criminal liability of perpetrators of self-defense resulting in loss of life, others seen from the Criminal Code and the analysis of the decision Number 61/Pid.B/2019/PN. CBD. This type of research is normative juridical, namely research based on law. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. Drawing conclusions in this paper is carried out using deductive-inductive logic of thinking that is done with the theory that is used as a starting point for conducting research. Keywords: Criminal Abolition, Self Defense, Life